2017
DOI: 10.1016/j.rboe.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the critical shoulder angle and the development of rotator cuff lesions: a retrospective epidemiological study

Abstract: ObjectiveTo perform a retrospective epidemiological study of radiographs in order to evaluate the relationship between the anatomy of the scapula and the development of rotator cuff injuries (RCIs).MethodsThis study retrospectively evaluated the relation of the critical shoulder angle (CSA) and RCIs from January 2011 to November 2013; patients were examined in the Orthopedics and Traumatology Department of a university hospital. The CSA was measured by radiographic standardization of two groups: a control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 16 publications
3
35
1
4
Order By: Relevance
“…This angular evaluation, however, does not take into account the forces of other muscles such as the pectoralis major, the latissimus dorsi and the biceps, which may also contribute to a more accurate predictability of mechanical shoulder overloads, 4 5 6 11 12 since muscle recruitment simplifications are used even in its theorizing. 11 12 13 Passive structures are also not taken into account this evaluation, as in the current models only at the extremes of movement they would have some influence on the forces acting on the shoulder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This angular evaluation, however, does not take into account the forces of other muscles such as the pectoralis major, the latissimus dorsi and the biceps, which may also contribute to a more accurate predictability of mechanical shoulder overloads, 4 5 6 11 12 since muscle recruitment simplifications are used even in its theorizing. 11 12 13 Passive structures are also not taken into account this evaluation, as in the current models only at the extremes of movement they would have some influence on the forces acting on the shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…Essa avaliação angular, entretanto, não leva em conta as forças de outros músculos como o peitoral maior, o grande dorsal e o bíceps, que também podem contribuir para uma previsibilidade mais precisa das sobrecargas mecânicas do ombro, 4 5 6 11 12 visto que simplificações do recrutamento muscular são utilizadas inclusive na sua teorização. 11 12 13 Estruturas passivas também não são levadas em conta nessa avaliação; pelos modelos atuais, apenas nos extremos de movimento elas teriam alguma influência nas forças atuantes no ombro.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Rotator cuff retraction can increase the tension of the repair, resulting in poor footprint coverage, and the more severe the rotator cuff retraction is, the longer the patient's disease course and the worse the tendon quality. 35,50,53 Studies have shown that the compression force and shear force of the shoulder joint depend on the CSA, 23,57 and the shear force of the joint increases as the CSA increases, which will cause the shoulder joint to become unstable. Thus, the supraspinatus muscle needs additional force to maintain the stability of the joint.…”
Section: Anatomic Factorsmentioning
confidence: 99%
“…CSAs above 35° (normal range 30°-35°) are associated with an increased risk of RC tear, which is thought to occur through altered deltoid biomechanics. 4 , 5 , 6 , 7 , 8 , 9 , 10 A high CSA results in a more vertical deltoid force vector through 2 mechanisms: (1) the longer acromion increases the lever arm of the deltoid, increasing its mechanical pull; (2) a larger glenoid inclination reduces the vertical deltoid force required to cause proximal migration of the humerus. 11 , 12 , 13 In the face of an increased vertical force vector, a larger compressive force is required by the RC to restore shoulder stability and prevent proximal humeral migration.…”
mentioning
confidence: 99%